Nativization of Fear and Anxiety as Identity in Selected Fiction of East African Asians - Wangila, Makhakha Joseph (International Journal of Scientific Research and Management (IJSRM), 2022)
This paper explores the concept of fear and anxiety in the identity formation process among East African Asians as captured in their selected works of fiction. It analyses identity and belonging by examining how emotions of fear and anxiety are presented in the selected texts through characterization and imagery. Using Bahadur Tejani's Day After Tomorrow , Peter Nazareth's In a Brown Mantle, M.G Vassanji's The In-between World of Vikram Lall and Imam Verji's Who will Catch Us as We Fall? the paper analyzes the changing trends and images of fear and anxiety among East African Asians, that make their interaction with the native Africans almost impossible. This paper is therefore geared towards exploring how the complexity of contemporary race relations between the Asians of East Africa and the native African communities, which is driven by fear and anxiety, find expression through literary narratives. In this paper I employ psychoanalytic theory in engaging with the texts owing to the emotional issues of fear and anxiety that makes it focus on the fragmented image of the Asian world and explore the alienated individual consciousness such as the interstitial position that the East African Asians find themselves in. I conclude that fear and anxiety play a role in the process of identity formation among East African Asians in their quest for belonging in the region.